The impact of cholesteryl ester transfer protein on the progression of cutaneous leishmaniasis - Batista-Dantas, Francisca Elda; Ozaki, Christiane Yumi; Santana, Kelly Gomes; Nunes, Valéria Sutti; Uscata, Bernardina Amorin; Siess-Portugal, Cinthia; Reis, Luiza Campos; Yamashiro-Kanashiro, Edite H.; Tafuri, Wagner Luiz; Duarte-Neto, Amaro Nunes; Sotto, Mirian Nacagami; Goto, Hiro; et al. (Frontiers in Immunology, 2024)
Pathogenesis of cutaneous leishmaniases involves parasite growth, persistent inflammation, and likely participation of lipoproteins. The cholesteryl ester transfer protein (CETP) has a role in lipoprotein metabolism and inflammation. We searched the lesion development in Leishmania (L.) amazonensis-infected human CETP transgenic-C57BL6/J mice (CETP). At 12 weeks of infection, CETP mice exhibited reduced lesion size, parasitism, and improved healing compared with infected control wild-type (WT) mice. We observed decreased CD68 + and increased CD163 + and CD206 + cells (M2 macrophage profile). The infected CETP mice displayed lower cholesterol levels in HDL and increased triglycerides in VLDL. Reduced CD36 receptor expression in the infected CETP mice correlated with healing and parasite reduction. In the in vitro experiment, the infected CETP macrophages showed lower parasite load, decreased arginase activity, and increased NO production compared with infected WT macrophages.Participation of CETP in Leishmania (L.) amazonensis infection development suggests its role in the modulation of immune response.